If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -2(3x + 6) = 3x + -1(2x + -16) Reorder the terms: 14 + -2(6 + 3x) = 3x + -1(2x + -16) 14 + (6 * -2 + 3x * -2) = 3x + -1(2x + -16) 14 + (-12 + -6x) = 3x + -1(2x + -16) Combine like terms: 14 + -12 = 2 2 + -6x = 3x + -1(2x + -16) Reorder the terms: 2 + -6x = 3x + -1(-16 + 2x) 2 + -6x = 3x + (-16 * -1 + 2x * -1) 2 + -6x = 3x + (16 + -2x) Reorder the terms: 2 + -6x = 16 + 3x + -2x Combine like terms: 3x + -2x = 1x 2 + -6x = 16 + 1x Solving 2 + -6x = 16 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + -6x + -1x = 16 + 1x + -1x Combine like terms: -6x + -1x = -7x 2 + -7x = 16 + 1x + -1x Combine like terms: 1x + -1x = 0 2 + -7x = 16 + 0 2 + -7x = 16 Add '-2' to each side of the equation. 2 + -2 + -7x = 16 + -2 Combine like terms: 2 + -2 = 0 0 + -7x = 16 + -2 -7x = 16 + -2 Combine like terms: 16 + -2 = 14 -7x = 14 Divide each side by '-7'. x = -2 Simplifying x = -2
| -4n-18=16 | | 44.91=9g+3.69 | | .15(10-x)+x=0.40(10) | | 45=d^2 | | 4t^2-5t-60=0 | | -35=-22-w | | 5x+20=9x-53 | | 49x^3-9x=0 | | 8x-8y=32 | | 2y-4(6)=-12 | | 0.5+3=x-2 | | 23=14-x | | .15(8-x)+x=0.40(8) | | (2+i)z-3+2i=0 | | Y^2+2.5y-9=0 | | 2x-y-4=13 | | (80x+60y)-(2x+30y)= | | -7(u+4)=-3u-16 | | 3x+x=y-18 | | 9x+4x+2=8x+3+4x | | -9=-6+x | | .10(8-x)+x=0.40(8) | | 12-2t=1-t | | -9=32x | | (4y+5)(6y-1)= | | 32-6x=12 | | 8v+2=12+3v | | 32-10x=12 | | 4(3x+6)=8(-6x-3) | | 0.45(19-x)+x=0.40(19) | | 3x^2+7x-28=2x^2-7x+4 | | 2t=5t-45 |